Hospital administration - Kane-Berman, Jocelyne Denise Lamrie (Department of Political Studies, 2017)
The Administrator of a hospital, particularly of a teaching hospital, is faced with the task of organising increasingly complex and specialised, high technology institutions, under constant pressure to improve patient care and community services, training of health personnel, and to seek new knowledge, therapies and techniques. In addition, acute general hospitals are being forced to re-examine their goals and functions in the light of greater competition from other health and social services for scarce resources - and of changing environmental circumstances. These activities must be undertaken in the context of new theories of management with greater emphasis on the psycho-social aspects of organisation, decision-making processes and advances in information-processing techniques. To be equipped for this task the hospital administrator must also acquire new knowledge and skills. It was therefore frustrating to discover that no training courses for hospital administrators, medical or otherwise were available in this country and that there was a dearth of literature with specific reference to the Republic. Thus, it was as a measure of desperation that this thesis was embarked on, in order to satisfy a personal need to learn about the theory of administration and to meet the need for basic research into, and documentation of, hospital administration in South Africa. In view of the necessity to study virtually every aspect of the subject and the fact that so little research had been done on the management of South African hospitals, it was felt that hospital administration should be examined as a totality rather than selecting any single aspect of the subject. General Systems theory which views any open system as a whole, in constant interaction with its environment, provided an appropriate conceptual framework for the general study of hospital administration. The Groote Schuur Hospital Group provided a suitable model within which to l examine the application of general systems theory; for analysis of the environment, resources, organisation and products of a hospital; and upon which to base some general conclusions regarding the administration of hospitals, recommendations for change and for further research. This thesis which is presented in eight chapters with a short summary of the contents at the end of each chapter has examined one teaching hospital group as a whole system. No attempt has been made to study any aspect of hospital administration in great detail, but rather to identify areas where immediate changes can be implemented to improve the effective and efficient utilisation of resources, and those where further research is essential to find better ways of achieving these goals and meeting societal needs. In the words of Tenon - The hospital is the conscience of a civilisation whose worth, in the end will be measured not by articles of faith and lofty doctrines but by the way it nurtures life; succours distress, rights injustices and transforms misery, frailty and want into hope, dignity and sufficiency.